Futures contracts as a type of securities transaction - Малишко, Володимир Миколайович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
This article regards important issues of modern stock relations - future contracts. The author revues origination history of future contracts, makes the definition, and individual distinctions from other stock contracts. The author makes conclusions considering future contracts application in Ukraine and improvements of the Ukrainian legislations in this sphere.